Current Treatment of Lower Gastrointestinal Hemorrhage - Raphaeli, Tal; Menon, Raman (Clinics in Colon and Rectal Surgery, 2012)
Massive lower gastrointestinal bleeding is a significant and expensive problem that requires methodical evaluation, management, and treatment. After initial resuscitation, care should be taken to localize the site of bleeding. Once localized, lesions can then be treated with endoscopic or angiographic interventions, reserving surgery for ongoing or recurrent bleeding.
Keywords: lower gastrointestinal hemorrhage; angiography; colonoscopy; gastrointestinal hemorrhage: surgery; radionuclide scintigraphy